Does mutualism drive the invasion of two alien species? The case of Solenopsis invicta and Phenacoccus solenopsis. - Aiming Zhou (Public Library of Science (PLoS), 2012)
Although mutualism between ants and honeydew-producing hemipterans has been extensively recognized in ecosystem biology, however few attempts to test the hypothesis that mutualism between two alien species leads to the facilitation of the invasion process. To address this problem, we focus on the conditional mutualism between S. invicta and P. solenopsis by field investigations and indoor experiments. In the laboratory, ant colony growth increased significantly when ants had access to P. solenopsis and animal-based food. Honeydew produced by P. solenopsis also improved the survival of ant workers. In the field, colony density of P. solenopsis was significantly greater on plots with ants than on plots without ants. The number of mealybug mummies on plants without fire ants was almost three times that of plants with fire ants, indicating a strong effect of fire ants on mealybug survival. In addition, the presence of S. invicta successfully contributed to the spread of P. solenopsis. The quantity of honeydew consumption by S. invicta was significantly greater than that of a presumptive native ant, Tapinoma melanocephalum. When compared with the case without ant tending, mealybugs tended by ants matured earlier and their lifespan and reproduction increased. T. melanocephalum workers arrived at honeydew more quickly than S. invicta workers, while the number of foraging S. invicta workers on plants steadily increased, eventually exceeding that number of T. melanocephalum foragers. Overall, these results suggest that the conditional mutualism between S. invicta and P. solenopsis facilitates population growth and fitness of both species. S. invicta tends to acquire much more honeydew and drive away native ants, promoting their predominance. These results suggest that the higher foraging tempo of S. invicta may provide more effective protection of P. solenopsis than native ants. Thus mutualism between these two alien species may facilitate the invasion success of both species.